Ectopic Gastric Mucosa in the Rectum: An Underrecognized Cause of Rectal Bleeding - Kıvrakoğlu, Fatih; Ergin, Mustafa; İbiş, Mehmet (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Kıvrakoğlu F, Ergin M, İbiş M. Ectopic gastric mucosa in the rectum: An underrecognized cause of rectal bleeding. Turk J Gastroenterol. 2025;36(9):618-619.